The integration of online marketing with optimization and community manager for SMEs at the international level for 2016 (GEON Journal (Management, Organizations and Business), 2016)
This article will show the emergence of a new community manager profession and the importance of online marketing in Europe and Latin America because the contents are the pillars of marketing and when carrying out the marketing strategy poses a structure and an organization that  will be oriented to the loyalty and conversion.Today it is still a research tool, healing and quality content. The international companies seeking to writing articles is optimization and is close to the reader and how important it is to create a marketing strategy or marketing visual content visual content, to transform the brand in action images that give a new dimension to the company.The contents with marketing generates excitement to the reader and to perform in a very visual way ideas and knowledge that the user receives is transmitted and adds value. This content marketing strategy is not conceived in isolation but is included within a larger plan in which all actions to be taken in the various fields, from social networks to parts of SEO is embodied; SEM among others.
Keywords: Content; marketing; writing; business online